2010
DOI: 10.1016/j.molcel.2010.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Induces G2 Cell-Cycle Arrest via mRNA Translation of the p53 Isoform p53/47

Abstract: p53 downstream pathways control G1 and G2 cell-cycle arrest, DNA repair, or apoptosis. However, it is still not clear how cells differentiate the cell-biological outcome of p53 activation in response to different types of stresses. The p53/47 isoform lacks the first 39 amino acids of full-length p53 including the Mdm2 binding site and the first trans-activation domain, and tetramers including p53/47 exhibit altered activity and biochemical properties. Here we show that endoplasmic reticulum stress promotes PER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
181
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(198 citation statements)
references
References 43 publications
15
181
2
Order By: Relevance
“…14-3-3σ was recently reported as a preferential Δ40p53 target gene. 5,14 Expressing Δ40p53 from the 14A-M2 plasmid resulted in a 70% increase in 14-3-3σ mRNA in H1299-NS cells (Figure 2e). However, SMAR1 knockdown greatly compromised the induction of 14-3-3σ mRNA with only about 17% increase in the H1299-S3 cells, suggesting that SMAR1 is required for Δ40p53-mediated transactivation ( Figure 2e).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…14-3-3σ was recently reported as a preferential Δ40p53 target gene. 5,14 Expressing Δ40p53 from the 14A-M2 plasmid resulted in a 70% increase in 14-3-3σ mRNA in H1299-NS cells (Figure 2e). However, SMAR1 knockdown greatly compromised the induction of 14-3-3σ mRNA with only about 17% increase in the H1299-S3 cells, suggesting that SMAR1 is required for Δ40p53-mediated transactivation ( Figure 2e).…”
Section: Resultsmentioning
confidence: 97%
“…37,38,[50][51][52][53][54] Our recent study showed that SMAR1 is directly linked to translation of both p53 and Δ40p53 in normal as well as glucose-deprived conditions.14-3-3σ was demonstrated as a preferential transcriptional target of Δ40p53. 5,14 The downstream effects of Δ40p53 induction on target gene activation, and the resulting biological outcome, have been previously explored. [55][56][57] In the current study, using Δ40p53-mediated transactivation as a model, we showed that SMAR1 is important for IRESdependent Δ40p53 induction, as well as for the consequent elevation of 14-3-3σ mRNA (Figure 2e).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suppression of PERK activity, 14-3-3s expression or deletion of the ER stress response IRES of p53/47 all result in an inhibition of UPR-induced G2/ M arrest. Together, this suggests that although p53/47 activates 14-3-3s, it also suppresses the induction of p21 CDKN1A/Cip1 and, thus, prevents the cells from arresting in G1/S while favouring a G2/M block (Bourougaa et al, 2010). In addition, expression of full-length p53 (p53FL) alone does not induce G2 arrest, but induces only GI arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Further work showed that suppression of PERK activity, through overexpression of either a dominant-negative PERK or small interfering RNA, resulted in the suppression of p53/47 expression, indicating that PERK is the signal transducer between the ER and p53/47 expression ( Figure 2) (Bourougaa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%